'[A]nother and yet the same': Rhyme's Music in Kubla Khan. Issue 2 (July 2017) - Reilly, Olivia
Abstract : In Biographia Literaria (1817) Coleridge described the 'sense of musical delight' and the 'power of producing it' as 'a gift of imagination', necessary to the poet. The correlation between poetry and music, essential to the formation of his poetics, he develops suggestively in the 'mingled measure' of 'Kubla Khan'. Paying close attention to the poem's intricate structure, this essay examines Coleridge's self-conscious construction in the poem of a complex patterning of aural connections and refrains. The exploration of rhyme's musical effect allows fresh insight into the poem, building upon previous interpretations to elucidate in particular the role of time, memory, and imagination in its realisation.